The Implementation of Value Clarification Technique (VCT) Learning Model to Improve Social Care Character in Social Science Learning - Khairunisa, Ninis (International Journal Pedagogy of Social Studies, 2017)
This study started from the problems that the author finds in class VIII-L SMP Negeri 29 Bandung where most students have not shown the character of social care. They are less concerned about others seen from behavior, such as: lack of respect to others, and less attention to the teachers and other students. Students seem individualistic and annoy or taunt their classmates with harsh words. From these findings, the author chose to do classroom action research (PTK) with Kemmis and Taggart model. Data analysis technique is qualitative and quantitative. In this study, the author makes observation as much as three cycles. In this study,value clarification technique (VCT) learning model is chosen to guide students to understand, clarify, and implement social care values in daily life including at class. In attempt to improve the students social care character, the author selects five indicators adjusted to the problems found at class. Based on the study that has been conducted, the result is obtained that: first, the planning that has been prepared by the author works well; second, the implementation of the VCT learning model is conducted three cycles with one action in the cycles 1 and 2 and two actions in cycle 3; third, it reflects the obstacles experienced by each cycle; fourth, the results obtained after implementing the VCT model to cycle 3 show that the students social care character has increased.